A Review on Theragnostic Applications of Micrornas and Long Non- Coding RNAs in Colorectal Cancer - Jothimani, Ganesan; Sriramulu, Sushmitha; Chabria, Yashna; Sun, Xiao-Feng; Banerjee, Antara; Pathak, Surajit (Current Topics in Medicinal Chemistry, 2018)
Colorectal cancer (CRC) is a heterogeneous malignancy leading to increased mortality and poor prognosis due to the lack of efficient early diagnostics. Metastasis of the tumor being the most common cause of mortality is accountable for almost 90% of CRC associated deaths. Intensified screening procedures and molecular target identification has inflated the median survival rate of in CRC patients. microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) have come forward as potential targets for developing a novel approach in CRC theragnostics. Non-coding RNA (ncRNAs) sequences are abundantly present and thereby play a vital role in several biological processes such as cellular organization, cell fate determination, proliferation, apoptosis, tissue homeostasis maintenance as well as pathological conditions such as cancer by acting as post transcriptional regulators of gene expression. Several studies have highlighted the involvement of these ncRNAs in CRC development. However, the molecular mechanism involved in regulating CRC has not been clearly elucidated. This review, throws light upon the several non-coding RNAs involved in CRC with a focus on novel mechanisms of action, recent advances in the regulatory mechanisms that control the gene expression related to carcinogenesis. Furthermore, the potential role of ncRNAs as diagnostic as well as therapeutic targets has been reviewed.
Keywords: Biomarker